(untitled) (Revista Escenarios Sociojurídicos, 2022)
The Colombian State had its first pronouncement regarding the right to die with dignity through Resolution No. 14437 of 1991, in which it recognized the right of all people to decide about their life due to the suffering of a terminal illness. Six years later, the Constitutional Court through Ruling C-239 of 1997, recognized the right to die with dignity as a fundamental right, considering the relationship between this right and the life with dignity and based on the constitutional principles of personal dignity, autonomy and solidarity. Also, it established the requirements that must be met for the exercise of the right. In 2014, in the absence of a law regulating the right, the Court, through Ruling T-970 dictated the measures to guarantee the right and orders the Ministry of Health and Social Protection to regulate them. In compliance with the order, the Ministry of Health issued the Resolution 1216 of 2015, which determines the procedure to be followed to enforce the right to die with dignity. Likewise, in Ruling T-544 of 2017, the Constitutional Court recognizes the right of minors taking into account the universal nature of human rights and the best interests of children and adolescents, which is duly consolidated in the domestic legal system. As a consequence, it reordered the Ministry of Health to regulate the procedure to guarantee the right this time including children and adolescents, so the Ministry issues Resolution 825 of 2018. Currently and despite repeated recommendations by the Constitutional Court, the Congress of the Republic has not issued any law regulating the matter. That opens the door to bureaucratic obstacles from health care providers when requesting the procedure to enforce the right to die with dignity, especially in children and adolescents.